2023
DOI: 10.3390/jof9050594
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of Cryptococcal Meningitis in Patients without Human Immunodeficiency Virus: Data from a Multi-Center Cohort Study

Abstract: Background: A clearer understanding is needed about the use of brain MRI in non-HIV patients with cryptococcal meningitis. Methods: Cerebral CT and MRI were studied in 62 patients in a multicenter study of cryptococcal meningitis in non-HIV patients. CT was performed in 51 and MRI in 44. MRI results are reported for the images read at NIH for 29 of the 44 patients. CT reports obtained from the original REDCap database were added to calculate the incidence of normal findings. Results: CTs were read as normal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
3
1
Order By: Relevance
“…Based on the imaging of the brain, we found that patients with CM with structural damage of the brain accounted for 60%, while patients with CM with non-structural damage of the brain accounted for 40%. This result is fairly different from the studies of Zhong et al [ 11 ] and Anjum et al [ 12 ], possibly due to regional and population differences. The levels of CSF-protein are considered an indicator of the severity of inflammation in the brain [ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Based on the imaging of the brain, we found that patients with CM with structural damage of the brain accounted for 60%, while patients with CM with non-structural damage of the brain accounted for 40%. This result is fairly different from the studies of Zhong et al [ 11 ] and Anjum et al [ 12 ], possibly due to regional and population differences. The levels of CSF-protein are considered an indicator of the severity of inflammation in the brain [ 49 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have identified two stages of pathogenic microorganism-induced CNS damage, where the first stage involves metabolic disorders [ 7 9 ], while the second involves structural lesions [ 10 ]. As per the results of previous experiments, structural damage of the brain was observed in 86.84–90.00% of patients with CM, while no structural damage of the brain was observed in the remaining patients [ 11 , 12 ]. Zhong et al demonstrated that the brain structure of patients with CM was normal in the early stage, manifesting only a few symptoms of nerve damage, followed by gradually appearing imaging changes, namely, structural damage [ 11 ].…”
Section: Introductionsupporting
confidence: 82%
“…When patients present with symptoms similar to those of cryptococcal intracranial infections, radiologic imaging should be performed to examine the intracranial situation, with MRI being more valuable than CT in this regard ( 11 ). The imaging manifestations of intracranial cryptococcal infection are diverse, including dilated Virchow-Robin (V-R) spaces and pseudocysts, cryptococcal granulomas (cryptococcomas), cornified nodules or patchy signals, meningitis with edema, and meningeal enhancement ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used imaging techniques in the central nervous system include computed tomography (CT), magnetic resonance imaging (MRI), and methods using radioactive tracers like positron emission tomography (PET) and single-photon emission computed tomography (SPECT). Existing clinical imaging modalities provide rapid and reliable assessment of brain disorders; however, they are often not specific to infections of the CNS [217,218]. As animal models are a valuable tool to understand the underlying mechanisms of CNS infections, non-invasive imaging of animal models has evolved into an important research tool in the biomedical sciences.…”
Section: Characterization Of Animal Models Of Cryptococcosis By In Vi...mentioning
confidence: 99%